2014
DOI: 10.1186/1756-3305-7-300
|View full text |Cite
|
Sign up to set email alerts
|

A case study of risk factors for lymphatic filariasis in the Republic of Congo

Abstract: BackgroundLittle is known regarding risk factors for lymphatic filariasis (LF) in Central Africa. We studied the epidemiology of LF in an endemic village in the Republic of Congo.MethodsDependent variables were Wuchereria bancrofti antigenemia (ICT card test) and microfilaremia (night blood smears). The following factors were investigated: sex, age, bed net, latrines, source of water, uptake of anthelmintic drugs, hunting/fishing activities, and occasionally sleeping in the bush. Mixed multivariate logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 36 publications
3
26
2
7
Order By: Relevance
“…In contrast, four rural districts having high MDA coverage were unable to stop LF transmission after five MDA rounds; we noted that these districts’ baseline LF prevalence was comparatively higher. Thus, MDA coverage is not the single factor that may determine the number of MDA rounds required to interrupt LF transmission, and other factors such as baseline LF prevalence, population density [ 29 ], occupation [ 30 ], personal hygiene [ 31 ], level of education and nutritional status [ 2 ] should be considered. Overall, our study showed the effective implementation of LF elimination efforts in Nepal, with some districts requiring additional MDA rounds to achieve LF transmission interruption.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, four rural districts having high MDA coverage were unable to stop LF transmission after five MDA rounds; we noted that these districts’ baseline LF prevalence was comparatively higher. Thus, MDA coverage is not the single factor that may determine the number of MDA rounds required to interrupt LF transmission, and other factors such as baseline LF prevalence, population density [ 29 ], occupation [ 30 ], personal hygiene [ 31 ], level of education and nutritional status [ 2 ] should be considered. Overall, our study showed the effective implementation of LF elimination efforts in Nepal, with some districts requiring additional MDA rounds to achieve LF transmission interruption.…”
Section: Discussionmentioning
confidence: 99%
“…The division of labor within and beyond the household and everyday practices intersects with other determinants such as age and socioeconomic status to affect exposure to NTD risks. For example, in contexts such as the Republic of Congo (where fishing, farming, hunting are the main income activities), prevalence of lymphatic filariasis (LF) in men is higher, especially where men sleep outside during these activities [12]. However, where people have similar occupational activities, such as agricultural work (as found in rural India), LF infection patterns among men and women were almost equal [13].…”
Section: Recommendation 1: Account For How Gender-related Division Ofmentioning
confidence: 99%
“…Hookworm infections, for example, appear to be more common in males (Behnke et al 2000;Pullan et al 2008) as is schistosomiasis (Pullan et al 2008). Filarial nematode infections show a higher prevalence in males (22.9 %) than females (12.6 %) in both rural (Chesnais et al 2014) and urban endemic regions (Mwakitalu et al 2014). Whether differences in the prevalence of nematode infections between men and women reflect differential host immunity, hormone levels, behavior, or a combination of factors must be empirically evaluated.…”
Section: Chaptermentioning
confidence: 99%